2023
DOI: 10.3389/fmed.2023.1114722
|View full text |Cite
|
Sign up to set email alerts
|

Present and future perspectives in early diagnosis and monitoring for progressive fibrosing interstitial lung diseases

Abstract: Progressive fibrosing interstitial lung diseases (PF-ILDs) represent a group of conditions of both known and unknown origin which continue to worsen despite standard treatments, leading to respiratory failure and early mortality. Given the potential to slow down progression by initiating antifibrotic therapies where appropriate, there is ample opportunity to implement innovative strategies for early diagnosis and monitoring with the goal of improving clinical outcomes. Early diagnosis can be facilitated by sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In comparison, Cutting et al 5 conducted a similar multi‐site registry‐based study and reported that 25.1% met their definition of fPF, with others reporting similarly higher estimates (summarized in Table 1). These variable estimates largely arise from: (1) the varying and evolving criteria used to define fPF, which range from the requirement for a definitive diagnosis of IPF in a family member (Froidure et al 3 ) to a broader set of criteria encompassing other interstitial lung diseases (ILDs) and related syndromic conditions 5,9 ; (2) the necessary reliance on the presenting patient's knowledge of detailed medical histories of their family members; and to a lesser extent; (3) the inevitable variability introduced by differences in study design, ascertainment and population differences. Further, we know that of patients presenting with ‘sporadic’ PF, ~10% are subsequently reclassified as fPF, as familial medical histories are re‐visited over time.…”
Section: Study Design Ascertainment Of Family History % Affected Case...mentioning
confidence: 99%
See 4 more Smart Citations
“…In comparison, Cutting et al 5 conducted a similar multi‐site registry‐based study and reported that 25.1% met their definition of fPF, with others reporting similarly higher estimates (summarized in Table 1). These variable estimates largely arise from: (1) the varying and evolving criteria used to define fPF, which range from the requirement for a definitive diagnosis of IPF in a family member (Froidure et al 3 ) to a broader set of criteria encompassing other interstitial lung diseases (ILDs) and related syndromic conditions 5,9 ; (2) the necessary reliance on the presenting patient's knowledge of detailed medical histories of their family members; and to a lesser extent; (3) the inevitable variability introduced by differences in study design, ascertainment and population differences. Further, we know that of patients presenting with ‘sporadic’ PF, ~10% are subsequently reclassified as fPF, as familial medical histories are re‐visited over time.…”
Section: Study Design Ascertainment Of Family History % Affected Case...mentioning
confidence: 99%
“…Highlighting the heterogenous nature of fPF, there are conflicting reports regarding whether fPF patients experience a more rapid decline in lung function and poorer transplant‐free survival 5,9 . Froidure et al 3 report that despite fPF patients being younger, with less exposure to smoke and more likely to be prescribed antifibrotic therapies, their lung function decline and transplant‐free survival were similar to that observed in sporadic IPF patients.…”
Section: Study Design Ascertainment Of Family History % Affected Case...mentioning
confidence: 99%
See 3 more Smart Citations